Associação do ângulo de fase padronizado com estado nutricional e desfechos clínicos em pacientes cirúrgicos oncológicos - Natalia Fenner Pena (2016)
The Standardized Phase Angle (AFP) is measured derived from electrical bioimpedance (BIA) adjusted for sex and age. AFP is able to assess the integrity of cell membranes and has recently been studied as a possible indicator of nutritional status (NS) and a prognostic factor in patients with cancer. However, few studies have evaluated the AFP's behavior as an indicator of nutritional status and adverse clinical outcomes in cancer patients. Objective: To evaluate the association between the AFP and the variables of the nutritional status preoperatively and clinical outcomes in cancer surgical patients. Methods: A longitudinal-prospective study of cancer surgical patients admitted to the Alfa Institute of Gastroenterology, Hospital das Clinicas in Belo Horizonte, Minas Gerais. The evaluation of the nutritional status of patients was performed before surgery (pre-operative) and clinical outcomes were evaluated postoperatively times until hospital discharge. The data on the nutritional status (NS) were obtained immediately preoperatively through the Subjective Global Assessment (SGA), arm circumference (AC), triceps skinfold (TSF), arm muscle area (AMA), percentage of weight loss (PPP) and functionality, the grip strength. The AFP was obtained by BIA and calculated according to the following equation: measured AFP = AF - AF average (for age and sex) / standard deviation of the population by age and sex. Data on clinical outcomes and blood glucose were collected from medical records and bed races. Descriptive and bivariate analyzes were performed; agreement between methods using the kappa coefficient and simple logistic regression models were used to evaluate the association between AFP, nutritional status and clinical outcomes in this population. To compare the mean blood glucose of the second categorization AFP, we used the ANCOVA. For all analyzes it was adopted a significance level of 5%; (p <0,05). Results: 121 patients were included in this study. The average age of participants was 58.8 ± 12.5 years, 52.9% male. The prevalence of malnutrition found according to the AGS was 63.6%, while 28.1% of patients had AFP values below the 5th percentile Preoperatively time, individuals classified second nutritional risk categorization of the AFP presented more likely to be malnourished according to AGS (OR = 3.66; 95% CI: 1.35 to 9.90), CB (OR = 4.24; 95% CI: 1.72 to 10.43) , AMB (OR = 4.38; 95% CI: 1.68 to 11.42), grip strength (OR = 3.84; 95% CI: 1.31 to 11.25) and have higher percentage of loss weight (PPP); (OR = 3.86; 95% CI: 1.64 to 9.06); (P <0.05). significant concordance was observed in the preoperative period, between the classification of AFP and AGS (0.29; p = 0.001), grip strength (0.25; p = 0.003) and AMB (0.24; p = 0.003). In relation to clinical outcomes has been identified high prevalence of infectious complications (57.0%) evaluated in cancer patients, and those classified at risk by AFP showed 3.51 (95% CI: 1.37 to 8.99; p = 0.009) times more likely, they have infectious complications during the hospital stay. No association was observed between the AFP and other outcome measures (p> 0.05). Conclusion: Our findings suggest that the AFP can be considered useful and earlier than traditional parameters, able to assist in the evaluation and classification of the nutritional status of cancer patients in the hospital. This also proved to be good prognostic indicator, capable of predicting infectious complications and showed a significant association tendency in relation to hyperglycaemia evaluated hospital. Future studies will confirm these findings and AFP, used in combination with other diagnostic tools in these patients nutritional, increase the sensitivity to detect more impaired nutritional status.